Endoscopic mucosal resection of a large inflammatory fibroid polyp (Vanek’s tumor): a case report: Resection of Vanek’s tumor - Buda, Carmelo; Garipoli, Claudia; Penna, Giuseppa; d'Aquino, Antonio; Galletti, Claudio; Facciolà, Alessio; Fedele, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Vanek’s Tumor (inflammatory fibroid polyp) is a rare benign mesenchymal lesion occurring throughout the digestive tract. Classical Vanek’s tumor (“gastric”) contains concentric formations of proliferating spindle cells, which are CD34 positive. Atypical-inflammatory pseudotumor-like Vanek’s tumor (“intestinal”) lacks concentric formations and is CD34 negative. A 70-years-old man patient presented during hematochemical routine tests, sideropenic anemia and leukopiastrinosis. The patient performed osteomyelitis biopsy and esophagogastroduodenoscopy (EGD) showing a gastric wall with nodular appearance and, in antrum pre-pyloric, a polypoid pedunculated lesion, measuring approximately 3 cm in diameter, surrounded by hyperemic mucosa. The lesion then was removed by en bloc endoscopic mucosal resection (EMR) and histo-morphological, immune-cytochemical and biomolecular evaluations were performed. The data were compatible with a benign polyp fibroid inflammatory (Vanek's Tumor). The results of this study suggest that endoscopic mucosal resection is a safe and efficacy solution for the resection of these gastrointestinal polyps and the two morphological patterns of Vanek’s tumor more probably represent only variants of one type of tumor than two different lesions. BRAF mutations were not shown growth PDGFRA wild-type Vanek’s tumor.